1999
DOI: 10.1038/sj.ejhg.5200362
|View full text |Cite
|
Sign up to set email alerts
|

A previously unrecognised phenotype characterised by obesity, muscular hypotonia, and ability to speak in patients with Angelman syndrome caused by an imprinting defect

Abstract: The clinical features of Angelman syndrome (AS) comprise severe mental retardation, postnatal microcephaly, macrostomia and prognathia, absence of speech, ataxia, and a happy disposition. We report on seven patients who lack most of these features, but presented with obesity, muscular hypotonia and mild mental retardation. Based on the latter findings, the patients were initially suspected of having Prader-Willi syndrome. DNA methylation analysis of SNRPN and D15S63, however, revealed an AS pattern, ie the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 15 publications
3
67
0
Order By: Relevance
“…Therefore, it is possible for some abnormal HECT-type E3s to cause muscular dystrophies. Actually, it has been reported that E6AP, another HECT-type E3, contributes to a severe neurological disorder, Angelman syndrome [24,25] which exhibits muscular hypotonia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible for some abnormal HECT-type E3s to cause muscular dystrophies. Actually, it has been reported that E6AP, another HECT-type E3, contributes to a severe neurological disorder, Angelman syndrome [24,25] which exhibits muscular hypotonia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Gillessen-Kaesbach et al 41 described the clinical phenotype in seven AS patients who presented initially with features of the Prader-Willi syndrome but were subsequently shown to have a chromosome 15 methylation pattern in keeping with AS. These patients presented with hypotonia, obesity, and a milder degree of mental retardation.…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…4 There are a small number of reported cases of patients with clinical features of PWS but a molecular diagnosis of AS. [5][6][7] In the majority of these cases partial loss of maternal methylation is observed.…”
Section: Introductionmentioning
confidence: 99%